Training Of Hand Ling Of Psychological Disorders For West Sumatera Soccer Referee - Muhammad Ar nando; Indri Wulandari (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2019)
The All Indonesia Football Association (PSSI) is a body that takes care of soccer in Indonesia. PSSI is an extension of the parent International organizations namely FIFA and AFC. PSSI has the duty to supervise, develop players and carry out Indonesian league competitions. A lot of efforts have been made by PSSI so that Indonesian football develops towards a better direction. These efforts include improving sports facilities and infrastructure, running tiered competitions, socializing game rules to the public and improving the quality of arbitration. One of the concerns of PSSI is improving the quality of referees. In general, the duties and responsibilities of soccer referees are to apply all the rules of the game when leading the match. If the referee can carry out their duties properly then it is expected that the match can run safely, smoothly, and in control. The partner's problems include: 1) Low referees knowledge of the types of psychological disorders and their remedies, 2) Referees do not really understand the use of media in the psychological handling of matches. The target of this activity is the referees of West Sumatra who have C2 (regional) and C1 (National) licenses of 100 people. The training model that can be given to referees to overcome the psychological problems of referees is given the following solutions: 1) The training and workshops to handle referees 'psychological disorders, 2) The training and workshops on the use of media in psychological referees' disorders. The purpose of this ac tivity is to increase the knowledge of West Sumatra football referees about the types of psychological disorders and how to overcome them, increase the knowledge of West Sumatra football referees about the use of media in handling psychological disorders in referees. The results of these activities concluded: 1) Increased knowledge and understanding of handling psychological disorders in referees, 2) Increased knowledge and understanding of the use of media in improving psychology before the match. This activity also produced articles that were published in the journal IS ISN.